FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP BELANJA MODAL (Studi Kasus Pemerintah Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2013-2015) - Ichda Septi Maulika, 14.05.52.0249; Maryono, Maryono (Students Journal of Accounting and Banking, 2018)
This Study aimed to analyze the factors that affect the capital expenditure. The independen variables this study the are original revenues, general allocation funds, profit sharing funds, and the rest of budget financing. The population in this study is the budget realization report of all districts/cities in central jawa province obtained from the Central Statistics Agency of Semarang city and the financial inspection body of Republic Indonesia representatives of Central Java year 2013-2015. Samples included in this research criteria as much 98 out of 105 file. By using purposive sampling. The method of data analysis used in this research is descriptive analysis and multiple linear regression analysis. The result of this study indicate that the original revenues have a positive and significant impact on capital expenditure, general allocation budget have a positive and significant impact on capital expenditure, revenue sharing has a positive and significant impact on capital expenditure, and the remaining budget financing has a negative and insignificant effect on spending capital.Keywords :Local Revenues, General Allocation Budget, Revenue Sharing Funds, The Rest The Budget Financing, Capital Expenditure.